Administrative and legal status of public administration subjects regarding countering terrorism: Constitutional and Theoretical Aspects - Opatsky, Roman; Pisotska, Karina; Chvaliuk, Andrii; Molchanov, Rostyslav; Tulinov, Valentyn (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
The research aimed to make known the administrative and legal status of public administration subjects in the counter-terrorism field. It was found that a rather straightforward and logical structure of state bodies in the field of organization and coordination of the fight against terrorism has been created in Ukraine. The system of anti-terrorist entities is a set of specific, legally defined institutions that interact intending to prevent, detect, stop and minimise the consequences of terrorist activities. The research used the following methods: analysis of biographical sources, synthesis, deduction, comparative analysis meta-analysis, etc. In the conclusions, it has been established that the President of Ukraine, the Verkhovna Rada and the Cabinet of Ministers are the key actors in the fight against terrorism in the system of higher authorities. The defining areas of action of the President of Ukraine in the sphere of counter-terrorism are the activities aimed at regulatory and legal support of counter-terrorism in Ukraine, which implies the creation, liquidation, reorganization and management of relevant counter-terrorism entities.